Trans Athletes are Athletes: The Struggle for Inclusion - Pastor, Aaren (Juniata Voices, 2025)
Dr. Pastor talks about the misguided controversy surrounding trans athlete inclusion in collegiate sports, revealing it as a political tool rather than a genuine threat. By using the National Collegiate Athletic Association's (NCAA) longstanding inclusion policies and critiquing misleading scientific studies, Pastor exposes the falseness of claims fueling trans sport bans. Throughout the lecture, the story of Lia Thomas, a transgender NCAA athlete, is used to compare her experience against the various current athletic policies of trans athletes. They ultimately promote a more nuanced understanding and caution against perpetuating baseless narratives that undermine the rightful inclusion of trans athletes in collegiate sports.